The effect of a healthy lifestyle programme on 8–9 year olds from social disadvantage. Issue 7 (9th June 2012) - Breslin, Gavin; Brennan, Deirdre; Rafferty, Ruth; Gallagher, Alison M; Hanna, Donncha
Abstract : Aims: This study assessed the efficacy of a school-based healthy lifestyle intervention (Sport for LIFE) for increasing physical activity, decreasing sedentary behaviour, reducing screen time behaviour, encouraging healthy attitudes and behaviour to nutrition, and reducing body mass index (BMI) in 8–9-year-old primary school children from lower socioeconomic backgrounds in Northern Ireland. Methods: A non-randomised controlled trial of 416 children from 24 schools took part. Schools were randomly assigned to one of two groups, an intervention or control group with 12 schools in each group. The intervention group received a 12-week school-based programme based on social cognitive theory. At baseline and follow-up, groups completed questionnaires assessing physical activity, screen time behaviour and dietary patterns. On each occasion anthropometric assessments of height and weight were taken. Physical activity and sedentary behaviour were measured by accelerometry. Results: Significant effects were observed for vigorous, moderate and light activity for the intervention group at follow-up. Sedentary behaviour was significantly reduced for the intervention group but not for the control group. No significant effects of the intervention on BMI, screen time behaviour or attitudes to nutrition, with the exception of non-core foods, were shown. Conclusions: The programme was effective in increasing physical activity and reducing sedentary behaviour, however no significant changes in screen time behaviour and attitude to nutrition, with the exception of non-core foods, were observed. Future research ideas are offered for tackling low levels of physical activity in children.